2014
DOI: 10.1177/230949901402200307
|View full text |Cite
|
Sign up to set email alerts
|

Early Reimplantation for Open Total Talar Extrusion

Abstract: Early reimplantation is recommended for open total talar extrusion, as it restores (to some extent) hind foot mechanics, heel height, and bone stock for activities of daily living and future reconstructive options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although AVN was the most common complication in their series, only one patient with deep infection developed collapse and needed arthrodesis. Mohindra et al 8 also recently reported good outcomes of primary reimplantation for talar extrusions in seven cases. At a mean follow-up of 31.9 months (24-46 months), three patients were able to walk without pain and three patients had mild-to-moderate pain.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although AVN was the most common complication in their series, only one patient with deep infection developed collapse and needed arthrodesis. Mohindra et al 8 also recently reported good outcomes of primary reimplantation for talar extrusions in seven cases. At a mean follow-up of 31.9 months (24-46 months), three patients were able to walk without pain and three patients had mild-to-moderate pain.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the most common perceived complication in this survey was AVN, which is also the most common complication reported in the literature. [7][8][9]12,13 It is also interesting to note that the majority of the participants were not aware of studies on talar extrusions with longterm outcomes. This emphasizes the need for such studies and multicenter or even international collaboration, to evaluate the outcomes and give more specific guidelines, as the individual experience of most surgeons is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors, to reduce the risk of infection, postpone talus reimplantation, and use talus-shaped antibiotic cement while waiting for cultural results and then talus implantation done in a staged procedure [ 9 ]. Recent studies suggest that immediate reimplantation with thorough irrigation of wound and debridement of tissue leads to lesser chance of probable postoperative complications such as infection and avascular necrosis [ 9 , 10 ]. We kept extruded talus for 10 min in diluted povidone-iodine solution to get rid of bacterial flora.…”
Section: Discussionmentioning
confidence: 99%